2016
DOI: 10.1111/ijfs.13115
|View full text |Cite
|
Sign up to set email alerts
|

Effect of extraction method and ripening stage on banana peel pigments

Abstract: Carotenoids are one of the most widespread pigments in nature and can be used as health-promoting natural food colorants. Banana peel, which is a by-product of banana processing, contains a range of bioactive compounds including carotenoids. There is no published research on the extraction of food-grade carotenoids from banana peels. This study evaluated the change in the banana peel carotenoid content over its ripening stages and determined the best possible solvent to extract carotenoid for food applications… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(12 citation statements)
references
References 24 publications
0
8
0
1
Order By: Relevance
“…When the fruits reached the ripening stage 1, central bunches of each genotype were harvested (2 bunches = 40 fruit) and they were stored at room temperature (20 ± 2 °C) and relative humidity (80 ± 2%), without ethylene treatment, until complete the desired ripening stage. The three ripening stages assessed, 2, 5 and 7, corresponded to the scale described by Soltani et al (2011) and Yan et al (2016) and were: stage 2 -all green; stage 5 -yellow with green ends; and stage 7 -yellow with brown areas.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…When the fruits reached the ripening stage 1, central bunches of each genotype were harvested (2 bunches = 40 fruit) and they were stored at room temperature (20 ± 2 °C) and relative humidity (80 ± 2%), without ethylene treatment, until complete the desired ripening stage. The three ripening stages assessed, 2, 5 and 7, corresponded to the scale described by Soltani et al (2011) and Yan et al (2016) and were: stage 2 -all green; stage 5 -yellow with green ends; and stage 7 -yellow with brown areas.…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, these parameters help to identify the best application for each genotype (e.g., banana for in natura consumption, banana candy, banana chips, banana pulp, among others). Studies have indicated that banana and plantain fruit contain appreciable quantities of antioxidant compounds, such as carotenoids (Yan et al 2016) and phenolic compounds (e.g. flavonoids).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies documented the existence of various carotenoids in banana fruit (Davey et al 2006). Although some suggested that the cultivars genotype specifies the quantity of carotenoids, they mostly concurred that the amount of trans-alpha and trans-beta carotene comprised the majority of pro-vitamin A compounds (Yan et al 2016). Another significant carotenoid reported was lutein, which exhibited antioxidant properties and an inhibitory effect on the age-related macular degeneration.…”
Section: Health Effects Of Banana Bioactive Compoundsmentioning
confidence: 97%
“…Other carotenoid compounds that belong to the xanthophyll group also contribute to the total carotenoids. However, they could hardly be found in the HPLC chromatogram due to an extremely low amount [7,[29][30][31].…”
Section: ■ Results and Discussionmentioning
confidence: 99%